Modeling the structural relationship between personality dimensions and attachment styles with communication skills and marital conflicts with the mediation of primary maladaptive schemas in couples facing divorce - Rahiman, Ruhollah; Qamari, Mohammad; Babakhani, Vahideh; Jafari, Alireza (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this research was to develop a model exploring the structural relationship between personality dimensions and attachment styles, communication skills, and marital conflicts, mediated by early maladaptive schemas in couples facing divorce. Method: This was a descriptive-correlational study. The population included all couples facing divorce who visited counseling centers in Takestan city during the second half of 2020 and 2021. A convenience sampling method was used, and the sample size was determined as 373 individuals based on Sample Power software. The research instruments included the Big Five Personality Traits Questionnaire, Communication Skills (Queendom, 2004), Marital Conflicts (Jones, 1997), Young’s Early Maladaptive Schemas (2007), and Hazan and Shaver’s Attachment Styles (1987). Data analysis was performed using SPSS and Amos software. Results: The results showed that personality dimensions do not significantly relate to marital conflicts among couples facing divorce (p<0.05). Similarly, attachment styles do not significantly relate to marital conflicts (p<0.05). However, early maladaptive schemas played a mediating role in the relationship between personality dimensions and marital conflicts, with a significant t-value (17.97) and significance level (p<0.05). Additionally, early maladaptive schemas had a mediating role in the relationship between personality dimensions and communication skills, indicated by a significant t-value (17.93) and significance level (p<0.05). Furthermore, early maladaptive schemas mediated the relationship between attachment styles and marital conflicts, with a t-value (12.87) and significance level (p<0.05). Conclusion: Considering that early maladaptive schemas can play a mediating role in the relationships of couples facing divorce, they are a significant factor in shaping personality, attachment styles, and marital conflicts.